Genetic Diversity - Bitz, Lidija (IntechOpen, 2017)
Genetic diversity is the entire amount of genes and genotypes in a group of organisms and is of vital importance for their adaptation to different living conditions. If, for example, all humans were identical, the extinction of the entire kind could happen very fast. Let us care and nourish differences! The goal of this book is to present some of the contemporary thoughts on understandings of the genetic diversity patterns and their altering in a changing world. The book is aimed to the ones inspired to study and contemplate genetic diversity and to the audience beyond any frames.